Effect of anisotropy coeficient on error rates of linear discriminant functions - Dučinskas, Kęstutis; Dreižienė, Lina (Lietuvos matematikos rinkinys, 2021)
Paper deals with statistical classification of spatial data as a part of widely applicable statistical approach to pattern recognition. Error rates in supervised classification of Gaussian random field observation into one of two populations specified by different constant means and common stationary geometric anisotropic covariance are considered. Formula for the exact Bayesian error rate is derived. The influence of the ratio of anisotropy to the error rates is evaluated numerically for the case of complete parametric certainty.
Keywords: geometric anisotropy; anisotropy ratio; Gaussian random field; equicorrelation; Bayesian discriminant function; actual error rate; expected error rate